Scientific literature on Inga (Fabaceae) from Santa Catarina state, Southern Brazil (1983-2017) - Antunes, Altamir Rocha; Elias, Guilherme Alves; Pezente, Gisele; Santos, Robson (Revista de Biología Tropical, 2019)
Inga Mill. belongs to mimosoid clado (Fabaceae, Caesalpinioideae) with 131 species in Brazil. It is the most expressive genus of Fabaceae. This study aimed to perform a bibliometric analysis on Inga from Santa Catarina state. A survey of the published literature was conducted using the electronic databases of the Web of Science, Scopus and Scielo, with the accepted names of Inga species and its synonyms. Papers were distributed in four subject categories: C1 (Ecological), C2 (morphology, anatomy, histology, physiology and genetics), C3 (production and use) and C4 (biochemical and nutritional properties). We registered 232 papers for 13 species of Inga, exhibiting remarkable growth over time. C1 was the most expressive subject category, mainly by nutrient supply, shading and nitrogen fixing capacity. The subjects diversifying over the years, with registered papers in all categories. Inga edulis, I. vera and I. marginata were the most registered species in our survey. We did not find papers on I. edwallii, I. sellowiana and I. vulpina. Our results showed an increase in the number of articles on Inga over time, especially in the last 13 years. However, some important gaps need to be addressed, such as the relatively small number and/or lack of studies conducted for some species.